2014
DOI: 10.5713/ajas.2013.13485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Barodon, an Anionic Alkali Mineral Complex, on Growth Performance, Feed Utilization, Innate Immunity, Goblet Cell and Digestibility in Olive Flounder (<italic>Paralichthys olivaceus</italic>)

Abstract: A 15-wk feeding trial was conducted to examine the supplemental effects of Barodon on growth performance, gastrointestinal histology, feed digestibility and innate immunity in olive founder. A basal commercial diet was used as a control and two other diets were prepared by spraying 0.1% or 0.2% of Barodon. Triplicate groups of fish (BW, 145 g) were fed one of the test diets to apparent satiation twice daily. At the end of the feeding trial, fish growth performance was not significantly affected by dietary trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
(39 reference statements)
4
16
0
Order By: Relevance
“…In agreement with the results of this study, natural mineral materials have been shown to enhance immune function in some previous studies (Koo ; Jurkić, Cepanec, Pavelić & Pavelić ; Shin et al . ). Lysozyme activity plays an important role in protecting the host from the infection by bacteria for the innate immunity in fish (Ellis ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In agreement with the results of this study, natural mineral materials have been shown to enhance immune function in some previous studies (Koo ; Jurkić, Cepanec, Pavelić & Pavelić ; Shin et al . ). Lysozyme activity plays an important role in protecting the host from the infection by bacteria for the innate immunity in fish (Ellis ).…”
Section: Discussionmentioning
confidence: 97%
“…This result is in agreement with Shin et al . () who reported the enhancement of serum lysozyme after dietary administration Barodon, an anionic alkali mineral complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Shin et al . ). Goblet cells in the gastrointestinal tract provide protection against damage by forming a viscous, hydrated blanket on the surface of the mucosa which acts as a sensitive first line of immune defence parameter in fish (Shin et al .…”
Section: Discussionmentioning
confidence: 97%